2021
DOI: 10.1007/s40122-021-00267-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of Cluster Headache: Clinical Variability, Persisting Pain Between Attacks, and Comorbidities—An Observational Cohort Study in 825 Patients

Abstract: Introduction: Cluster headaches can occur with considerable clinical variability. The interand intra-individual variability could contribute to the fact that the clinical headache phenotype is not captured by too strict diagnostic criteria, and that the diagnosis and the effective therapy are thereby delayed. The aim of the study was to analyze the severity and extent of the clinical symptoms of episodic and chronic cluster headaches with regard to their variability and to compare them with the requirements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…There is a slight preponderance for right-sided attacks in cluster headache. 25 Taken together with better responses in those with right-sided attacks, it suggests that the pain neuromatrix may have some form of lateralization which both makes patients more prone to right-sided attacks and more likely to respond to treatment if attacks are right-sided. We hypothesized that patients with comorbid affective disorders or other chronic pain conditions may be less likely to respond because these has been shown to be negative predictive factors of response to occipital nerve stimulation for chronic headache disorders, but this was not borne out by the results.…”
Section: Discussionmentioning
confidence: 99%
“…There is a slight preponderance for right-sided attacks in cluster headache. 25 Taken together with better responses in those with right-sided attacks, it suggests that the pain neuromatrix may have some form of lateralization which both makes patients more prone to right-sided attacks and more likely to respond to treatment if attacks are right-sided. We hypothesized that patients with comorbid affective disorders or other chronic pain conditions may be less likely to respond because these has been shown to be negative predictive factors of response to occipital nerve stimulation for chronic headache disorders, but this was not borne out by the results.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent pain between attacks and allodynia, which are prevalent among CH patients, refs. [40][41][42] indicate increased sensitivity. The chronology of central sensitization in CH is unstudied; in particular, we do not know whether sensitization precedes the bout or is a consequence thereof.…”
Section: Sensitizationmentioning
confidence: 99%
“…This results in a limited understanding of the triggers and temporal course of the condition. 3,5 Variability in the clinical presentation, 6 misdiagnosis of symptoms as being migraine-related, 7 and the lack of understanding and awareness, 8 particularly among primary care physicians, contribute to diagnostic delays of several years for most patients with cluster headache. 7,9 A recent study identified that up to 50% of patients were diagnosed with cluster headache by a neurologist, indicating that misdiagnosis or inappropriate treatment may have come from other specialists or self-diagnosis.…”
Section: Introductionmentioning
confidence: 99%